REASONS FOR GENERAL JURABEK’S TRANSFER TO THE SERVICE OF THE RUSSIAN EMPIRE - Parmonov Sharofiddin Shavkatovich (Next Scientists Conferences, 2025)
This article analyzes the reasons for Major General Jurabek Qalandar Qori oglu's transfer to the service of the Russian Empire, as well as the relationship between Khudoyorkhan and the beks, based on sources.